Menopause : A Comprehensive Approach - Cano, Antonio (Springer International Publishing : Imprint: Springer, 2017)
This book provides an evidence-based approach to the universal experience of menopause. Its structured format clearly separates the biological basis from the clinical impact and quality of life, while also examining menopause within the context of healthy ageing in females. Accordingly, the book addresses factors including lifestyle, frailty, sarcopenia, and new ICT technologies. Written by respected experts in the field, the book offers a valuable guide for gynecologists and professionals devoted to women's healthcare and ageing quality of life, while also sharing revealing insights for non-professionals.
Keywords: Medicine.; Gynecology.; Internal medicine.; Nursing.; elektronické knihy; electronic books